Pola Persebaran dan Keanekaragaman Kelomang di Zona Litoral Pantai Leuweung Sancang Kabupaten Garut - Cinthiya O. B. A. Fau; Diana Hernawati; Diki Muhamad Chaidir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The littoral zone of Leuweung Sancang Beach, Garut Regency has very diverse biodiversity, such as hermit crabs. This study aims to determine the distribution patterns and species diversity of hermit crabs in the littoral zone of Leuweung Sancang Beach. This research was conducted from February 2022 to June 2022. This research uses quantitative methods and sampling techniques using a 100 meter transect belt which is divided into 100 plots with a size of 1 x 1 meter. The stations used are Cibako 1 station, Cikujang Jambe 2 station, and Ciporeang 3 station. The results of this study obtained data on the distribution pattern of hermit crabs on Leuweung Sancang Beach, namely clusters with an id value > 1 obtained data on the diversity of hermit crabs consisting of 3 family, 5 genus, and 13 species. The results of the calculation of the ecological index on hermit crabs show that the average density of hermit crab species is 15.73 ind/m2, the average diversity index is 1.27 includes the moderate diversity category, the average uniformity index is 0.52 includes the moderate uniformity category, and the average dominance index is 0.39 includes the category of moderate dominance.